Integrating STEM project into mathematics learning design to improve the students’ mathematical literacy - Nita Hidayati; Attin Warmi; Hanifah Hanifah; Latifah Darojat; Shahrun Niza Sofian; Epin Hidayat (International Journal on Education Insight, 2026)
Students need to develop sufficient mathematical literacy. In reality, however, not all students demonstrate good mathematical literacy. The project-based learning (PjBL) model is a recommended teaching model, then STEM is a broad approach. This echo produces a STEM-integrated project learning model. Based on this description, researchers designed and developed Local Instructional Theory (LIT) in the form of mathematics learning with a STEM-integrated project learning model on the topic of lines and angles. This study uses a design research method, which includes three research stages: preliminary, teaching experiment, retrospective analysis. The research subjects were students taking Geometry courses. Data collection techniques used were interviews, documentation, field notes, and written tests that were collected and analyzed to improve HLT. This study was designed in three activities: creating a Joglo house project with maximum STEM-based enlightenment, identifying the concept of lines and angles and measuring angle sizes, then categorizing the types of angles and understanding the relationships between angles. From the results of all the activities that have been carried out, the learning trajectory provides students with activities that are enthusiastic in learning, creative in creating, active in discussions, and group learning to complete an assigned project. The use of LIT produces a design that has a strong theoretical basis because each learning syntax is compiled based on a synthesis of various theories and empirical research results, then validated through research and development stages.